2015
DOI: 10.1007/s00704-015-1492-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of rainfall trends of Sri Lanka

Abstract: This study was based on daily rainfall data of 48 stations distributed over the entire island covering a 30-year period from 1981 to 2010. Data analysis was done to identify the spatial pattern of rainfall trends. The methods employed in data analysis are linear regression and interpolation by Universal Kriging and Radial Basis function. The slope of linear regression curves of 48 stations was used in interpolation. The regression coefficients show spatially and seasonally variable positive and negative trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…Insignificant decreasing rainfall trend is observed in Labukelle-estate station. However, Chandrasekara and Prasanna [29] and Wickramagamage [32] showed that there are predominant negative trends in the annual rainfall of central highlands including the study stations. Therefore, increase in rainfall in the JJAS season has low influence on the annual rainfall of the selected stations.…”
Section: Rainfall Trend Analysis According To the Data Resultsmentioning
confidence: 99%
“…Insignificant decreasing rainfall trend is observed in Labukelle-estate station. However, Chandrasekara and Prasanna [29] and Wickramagamage [32] showed that there are predominant negative trends in the annual rainfall of central highlands including the study stations. Therefore, increase in rainfall in the JJAS season has low influence on the annual rainfall of the selected stations.…”
Section: Rainfall Trend Analysis According To the Data Resultsmentioning
confidence: 99%
“…However, they found that the intensity of rainfall was increasing. In addition, Ranatunge et al (2003), Jayawardene et al (2005), Wickramagamage (2016) and Karunathilaka et al (2017) have put efforts in studying annual and seasonal rainfall trends in Sri Lanka. (Khaniya et al 2018) presented some interesting rainfall trend analyses and linked them with the hydropower generation of a ROR hydropower plant.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers rely largely on inter-monsoonal and monsoon rains, thus placing them at substantial risk of crop failure in years when rainfall is limited or delayed [61]. Several authors have shown that rainfall in Sri Lanka declined during the latter half of the 20th century [62][63][64]. Domroes and Schaefer [65] suggest that the estimated average annual rainfall declined from 2005 mm during 1931 to 1960, to 1861 mm (7.2%) during 1961 to 1990.…”
Section: Direct Effectsmentioning
confidence: 99%